Knowledge on prevention of breast cancer among females attending outpatient department of All India Institute of Medical Sciences, Jodhpur, Rajasthan - Nebhnani, Mamta Rajput; Phalswal, Uma; Ohri, Uma; Raj, Shalini; ., Vineeta; ., Suman; Singh, Shivangi (International Journal Of Community Medicine And Public Health, 2021)
Background: Breast cancer is the most common cancer and principal cause of death among females. Breast cancer related awareness and practices of female are known to have crucial contribution in the prevention. The aim of the study was to assess knowledge on prevention of breast cancer among females. Methods: This descriptive study was conducted on females attending outpatient departments of All India Institute of Medical Sciences, Jodhpur, Rajasthan. 70 females within age group of 15-60 year were enrolled in the study via convenience sampling technique. Data was collected through face-to-face interview. Reliability of self-structured knowledge questionnaire was determined by KR 20 method and found reliable (0.84). Data collected was analyzed for frequency, mean, standard deviation and test. Results: Findings showed that most (51%) of the respondents were from age group 15-30 years. Only 14% of the subjects had family history of breast cancer. Most of the subject (81.4%) previously heard about breast cancer. The mean knowledge score was 14.43±2.9. Most of the respondents (74.3%) had average knowledge about prevention of breast cancer whereas only 3% had excellent knowledge levels. Knowledge of subjects about prevention of breast cancer was found to have significant association with level of education and area of living only. Conclusions: Result of the study provided information that maximum number of participants had average knowledge about different aspects about prevention of breast cancer. The knowledge of females was significantly associated with their educational status.